2004
DOI: 10.1111/j.1462-2920.2004.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the archaeal community in 44 anaerobic digesters as determined by single strand conformation polymorphism analysis and 16S rDNA sequencing

Abstract: The diversity of Archaea in anaerobic digesters was characterized by strand conformation polymorphism (SSCP) analysis and the sequencing of 16S rDNA genes. The 44 digesters sampled, located in eight different countries, treated effluents from agriculture, the food processing and petro-chemical industries, pulp and paper plant, breweries, slaughterhouses and municipal waste. All the existing processes were represented among the samples (fixed-film, fluidized bed, stirred-tank, UASB, sequential batch reactor, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 45 publications
10
134
2
1
Order By: Relevance
“…Currently, the only genera known to use acetate for methanogenesis are Methanosarcina and Methanosaeta. However, Methanosarcina failed to inhabit in the anaerobic sewer biofilms, which is consistent with the finding that usually only one acetoclastic methanogen dominates such anaerobic environments (60). It is likely that Methanosaeta out-competed Methanosarcina due to differences in their affinities for acetate.…”
Section: Discussionsupporting
confidence: 77%
“…Currently, the only genera known to use acetate for methanogenesis are Methanosarcina and Methanosaeta. However, Methanosarcina failed to inhabit in the anaerobic sewer biofilms, which is consistent with the finding that usually only one acetoclastic methanogen dominates such anaerobic environments (60). It is likely that Methanosaeta out-competed Methanosarcina due to differences in their affinities for acetate.…”
Section: Discussionsupporting
confidence: 77%
“…Our knowledge about the microbial consortia involved in this process is limited because of a lack of phylogenetic and metabolic data on these predominantly uncultivated microorganisms. As an alternative to culture techniques, several molecular inventories, based on the study of the 16S rRNA gene, were carried out on anaerobic environments and have shown the extent of the diversity in these complex ecosystems (Godon et al, 1997a, b;Sekiguchi et al, 1998;Leclerc et al, 2004;Chouari et al, 2005a). These studies have limitations in that they often focused on one type of process, one sample, and often only lab-scale units.…”
Section: Introductionmentioning
confidence: 99%
“…According to these studies, the 16S rRNA gene clones retrieved from UASB sludges indicated the major microbial constituents to be those of the phyla Proteobacteria, Chloroflexi, Firmicutes, Spirochaetes, and Bacteroidetes in the domain Bacteria, and those of the classes Methanomicrobia, Methanobacteria, and Thermoplasmata in the domain Archaea (47). In addition, such studies have also shown that a large number of the clones assigned to candidate phyla (known as 'clone clusters') were frequently found in such ecosystems (7,8,10,20,31,48,55). However, there are still obstacles to precisely determining and monitoring the entire microbial community of sludge because of the limited number of datasets reported so far.…”
mentioning
confidence: 99%
“…So far, molecular-based community analyses have been performed for UASB granular sludges treating wastewater from a paper factory (41), a terephthalatemanufacturing plant (53), a beer brewery (13), and sucrose/ propionate/acetate-based artificial wastewater (44). In addition, the molecular characterization of UASB granules targeting specific microbial groups has also been reported (10,20,31). According to these studies, the 16S rRNA gene clones retrieved from UASB sludges indicated the major microbial constituents to be those of the phyla Proteobacteria, Chloroflexi, Firmicutes, Spirochaetes, and Bacteroidetes in the domain Bacteria, and those of the classes Methanomicrobia, Methanobacteria, and Thermoplasmata in the domain Archaea (47).…”
mentioning
confidence: 99%